Does Corruption Effects on Social Sector in SAARC Region? (Journal of Asian Development Studies, 2013)
The objective of this paper is to assess the impact of corruption on social sector in SAARC region countries using the panel data of four member countries between the periods 1991-2010. We use corruption, tax revenues and FDI as independent variable and education index as dependent variable. The paper uses simple Ordinary Least Square (OLS) technique as methodology for empirical findings. The analysis clearly indicates that corruption control has a positive relation with education. As corruption is controlled provision of services of education to social sector would be better. As well as tax revenues and foreign direct investment is also positively related to education sector. So to make better provision of education services to social sector and to increase adult literacy rate and gross enrollment ratio corruption should be controlled and expenditures on education sector by tax revenues should be increase because it will lead to development.